2013
DOI: 10.1002/ejlt.201300320
|View full text |Cite|
|
Sign up to set email alerts
|

Reduction of high oleic sunflower oil to glyceryl trioleyl ether

Abstract: "High oleic" sunflower oil was converted into the respective triether using InBr 3 or GaBr 3 as catalysts and triethylsilane or 1,1,3,3-tetramethyldisiloxane (TMDS) as reducing agent in solvent-free reactions. GaBr 3 /TMDS was found to be the most efficient reduction system enabling to carry out the reduction at room or moderately elevated temperature using stoichiometric amounts of TMDS and low amounts of the catalyst (0.005-0.01 eq. Ga/ester functionality). The conversion of the starting material was 100% yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 27 publications
2
7
0
5
Order By: Relevance
“…The more pronounced degradation for polyethers 2 i and 2 j might be related to the close proximity of the ester groups. As comparison, the GaBr 3 ‐catalyzed reduction of triglycerides, which contain neighbouring oxygen atoms, showed about 7 % reduction per ester unit to the alcohol, which is in agreement with the reduction of 1 i and 1 j . An influence of the methyl group in α‐position to the ester functionality can be excluded, as the reduction of 1 l to 2 l did not result in excessive cleavage.…”
Section: Methodssupporting
confidence: 78%
See 2 more Smart Citations
“…The more pronounced degradation for polyethers 2 i and 2 j might be related to the close proximity of the ester groups. As comparison, the GaBr 3 ‐catalyzed reduction of triglycerides, which contain neighbouring oxygen atoms, showed about 7 % reduction per ester unit to the alcohol, which is in agreement with the reduction of 1 i and 1 j . An influence of the methyl group in α‐position to the ester functionality can be excluded, as the reduction of 1 l to 2 l did not result in excessive cleavage.…”
Section: Methodssupporting
confidence: 78%
“…[12] In the typical synthesis of 2j by cationic polymerization of 2-methyloxacyclobutane, am ixture of head-to-head, tail-to-tail, and head-to-tail additions is obtained. [11a] Although the molecular weights of the here obtained 2i (M n = 300 gmol À1 )a nd 2j (M n = 800 gmol À1 )a re rather low, they might still be used as polyols for the synthesis of polyurethanes.T he more pronounced degradation for polyethers 2i and 2j might be related to the close proximity of the ester groups.A sc omparison, the GaBr 3 -catalyzed reduction of triglycerides,w hich contain neighbouring oxygen atoms, showed about 7% reduction per ester unit to the alcohol, [7] which is in agreement with the reduction of 1i and 1j.A n influence of the methyl group in a-position to the ester functionality can be excluded, as the reduction of 1l to 2l did not result in excessive cleavage.T he result of the GPC analysis of polypropylene oxide 2i was confirmed by mass spectrometry (ESI-MS) showing the main peak at m/z = 315.2354 (C 15 H 32 LiO 6 )c orresponding to five monomer units.…”
Section: Angewandte Chemiesupporting
confidence: 74%
See 1 more Smart Citation
“…Auf diese Weise sind die entsprechenden α,ω‐Dienether einfach herstellbar . Außerdem konnten Triglyceride zu den entsprechenden Glycerintrialkylethern reduziert werden . Weitere Reduktionsmethoden wurden kürzlich zusammengefasst .…”
Section: Methodsunclassified
“…We showed that the ω,ω′ ‐unsaturated ether monomers can be synthesized from renewables via Williamson ether synthesis, although the overall sustainability of this approach is lacking . To provide a more sustainable procedure, we recently introduced the GaBr 3 ‐catalyzed reduction of an ω,ω′ ‐unsaturated ester to the respective ether, which also was used for the synthesis of ethers with other applications than polymer chemistry . Additionally, we recently demonstrated that this catalytic method can be used to directly reduce polyesters to polyethers, obtaining structurally simple, yet to since recently unknown polyethers .…”
Section: Introductionmentioning
confidence: 99%